Familial Follicular Cell-Derived Thyroid Carcinoma - Son, Eun Ju; Nosé, Vania (Frontiers in Endocrinology, 2012)
Follicular cell-derived well-differentiated thyroid cancer, papillary (PTC) and follicular thyroid carcinomas (FTC) compose 95% of all thyroid malignancies. Familial follicular cell-derived well-differentiated thyroid cancers contribute to 5% of those cases. These familial follicular cell derived carcinomas or non-medullary thyroid carcinomas (NMTC) divide into two clinical-pathological groups. One group, syndromic-associated, composed by predominately non-thyroidal tumors, is comprised of Pendred syndrome, Warner syndrome, Carney complex type 1, PTEN-hamartoma tumor syndrome (Cowden disease; PHTS), familial adenomatous polyposis (FAP)/Gardner syndrome. Additionally other less established links correlated to the development of follicular cell-derived tumors have also included Ataxia-teleangiectasia syndrome, McCune Albright syndrome, and Peutz-Jeghers syndrome. The subsequent group encompasses syndromes typified by non-medullary thyroid carcinomas or NMTC, as well as, pure familial (f) PTC with or without oxyphilia, fPTC with multinodular goiter and fPTC with papillary renal cell carcinoma. This heterogeneous group of diseases has not a established genotype-phenotype correlation as the well-known genetic events identified in the familial C-cell-derived tumors or medullary thyroid carcinomas (MTC). Clinicians should be have the knowledge to identify the likelihood of a patient presenting with thyroid cancer having an additional underlying familial syndrome stemming from characteristics through morphological findings that would alert the pathologist to have the patient undergo subsequent molecular genetics evaluations. This review will discuss the clinical and pathological findings of the patients with familial papillary thyroid carcinoma, such as familial adenomatous polyposis, Carney complex, Werner syndrome, and Pendred syndrome and the heterogeneous group of familial papillary thyroid carcinoma.